"Hanging in a balance": A qualitative study exploring clinicians' experiences of providing care at the end of life in the burn unit. (February 2021) - Bayuo, Jonathan; Bristowe, Katherine; Harding, Richard; Agbeko, Anita Eseenam; Wong, Frances Kam Yuet; Agyei, Frank Bediako; Allotey, Gabriel; Baffour, Prince Kyei; Agbenorku, Pius; Hoyte-Williams, Paa Ekow; Agambire, Ramatu
Background: Although the culture in burns/critical care units is gradually evolving to support the delivery of palliative/end of life care, how clinicians experience the end of life phase in the burn unit remains minimally explored with a general lack of guidelines to support them. Aim: To explore the end of life care experiences of burn care staff and ascertain how their experiences can facilitate the development of clinical guidelines. Design: Interpretive-descriptive qualitative approach with a sequential two phased multiple data collection strategies was employed (face to face semi-structured in-depth interviews and follow-up consultative meeting). Thematic analysis was used to analyze the data. Setting/participants: The study was undertaken in a large teaching hospital in Ghana. Twenty burn care staff who had a minimum of 6 months working experience completed the interviews and 22 practitioners participated in the consultative meeting. Results: Experiences of burn care staff are complex with four themes emerging: (1) evaluating injury severity and prognostication, (2) nature of existing system of care, (3) perceived patient needs, and (4) considerations for palliative care in burns. Guidelines in this regard should focus on facilitating communication between the patient and family and staff, holistic symptom management at the end of life, and post-bereavement support for family members and burn care practitioners. Conclusions: The end of life period in the burn unit is poorly defined coupled with prognostic uncertainty. Collaborative model of practice and further training are required to support the integration of palliative care in the burn unit.